Analysis Of Financial Performance Quality Influenced By Financial Literacy And Internal Control Systems Moderate By Internal Audit In The Convection Business - Djoewita Djoewita; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (International Journal of Economics and Management Research, 2023)
This research aims to analyze and test the influence of the internal control system and financial literacy moderated by internal audit to obtain the quality of SME financial performance. The convection data in the city of Malang is a population of 30 convection shops, while all those who answered the questionnaire were collected using the questionnaire method, namely by providing a list of questions sent to 60 respondents in the finance department. The technical analysis of this research uses moderated regression analysis calculated using SPSS software. The research results show that the influence of financial literacy and the internal control system moderated by internal audit has proven to be positive and significant on the quality of financial performance.